Securing electrical substation's wireless messaging with a lightweight crypto-algorithm IP core - Abbas Y.A.; Jidin R.; Jami N.; Z'aba M.R. (Institute of Electrical and Electronics Engineers Inc., 2023)
Monitoring assets such as remote electrical substations and remote small power stations often pose challenges to utility companies. Often, cheap solutions to monitor and to provide an online control for these assets are by means of cellular. However, using this kind of communication requires proper security measures, but not at the expense of cost. Therefore, to improve security of wireless communication of these remote assets, we would like to propose a light-weight crypto-algorithm in the form hardware circuits called IP core. The crypto-algorithm has been implemented within an environment of microprocessor system on a XILINX Field Programmable Logic Arrays chip. A complete microprocessor system consists of Micro-Blaze processor, memory, serial communication and a light-weight crypto-algorithm can be fitted on a single XILINX VIRTEX chip. We have tested the system with a simplified version of the crypto-algorithm on a VIRTEX evaluation board, using GSM modems communicate over a cellular network. © 2014 IEEE.